Integration of Buton Cultural Values Through Wolio Language Towards Cultural Identity Awareness and Social Studies Learning - Suarni, Suarni; Wahyudianto, Tri; Surjati, Endang (Fakultas Keguruan dan Ilmu Pendidikan, ULM, 2026)
Globalization and modernization have caused an identity crisis among the younger generation. This brings a strong influence of foreign cultures, causing local values, lifestyles, and cultural orientations to shift gradually. Education plays a crucial role in reinstilling a sense of cultural identity. The purpose of this study is to analyze the process of integrating Butonese cultural values through the use of Wolio in social studies learning and the impact of this integration on the cultural identity awareness of ninth-grade students at SMP Negeri 2 Baubau, Southeast Sulawesi. The research approach uses a qualitative research type with a case study design. Data collection methods include observation, interviews, and documentation. The research subjects include ninth-grade students and social studies teachers at SMP Negeri 2 Baubau. Sampling was carried out using purposive sampling and snowball sampling techniques. Data analysis includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that the integration of Butonese cultural values into social studies learning is effective through various strategies such as folktales and proverbs. This confirms that the integration of Butonese cultural values through Wolio language in learning plays an important role as a learning medium that supports the installation of students' cultural identity awareness.